HUMANITARIAN CRISIS AND DIGITAL ADVOCACY: UNPACKING THE ALL EYES ON RAFAH CAMPAIGN - Teguh Luhuringbudi; Purnama Putra; Fitri Liza; Mowafg Abrahem Masuwd; Dewi Nita Utami; Abdulnasir Dhaw Alsayd (QAULAN: Journal of Islamic Communication, 2025)
The "All Eyes on Rafah" campaign, featuring an AI-generated image of a refugee tent formation spelling out the campaign's name, has emerged as a pivotal instance of global digital advocacy. This study examines the campaign in the context of Israel's devastating bombing of Palestinian refugee tents in Rafah, which resulted in significant civilian casualties. The research investigates how digital media and AI-generated imagery shape international humanitarian responses. Employing a qualitative, descriptive, and interdisciplinary approach, the study analyzes primary data sources through various theoretical frameworks, including viral images and news reports. The findings illuminate the transformative role of digital advocacy in influencing global perceptions and mobilizing humanitarian action, highlighting the potential of AI in such campaigns. This research contributes valuable insights to the media, political communication, and international relations fields. However, it is limited by its focus on a single case, indicating the necessity for further exploration of AI's broader implications in media and communication. Keywords: Humanitarian Crisis; Digital Advocacy; All Eyes on Rafah; Campaign.